Analisis Cost Efficiency Bank Umum di Indonesia Selama Pandemi Covid-19 Periode 2020-2022 - Putri, Habibatuz Akbaricha; Maski, Ghozali (Universitas YARSI, 2023)
The condition of the Covid-19 pandemic had an impact on the banking sector which caused a decline in bank performance in 2020 as indicated by a decrease in ROA of 35.63%, an increase in BOPO of 9.06%, and an increase in NPL of 20.95% (yoy). This study aims to estimate banking cost efficiency during economic conditions during the Covid-19 pandemic for the period 2020 – 2022. The sample of this study was 40 bank companies listed on the Indonesia Stock Exchange during the study period. The research method used is stochastic frontier analysis (SFA) to estimate the cost efficiency of a bank and principal component regression to estimate the determinant of a bank’s cost efficiency. It was found that the average cost efficiency of banks in Indonesia has increased every year by 0.720925 in 2020, 0.773875 in 2021 and 0.818744 in 2022 respectively. The factors that affects cost efficiency is NPL and LDR are significantly negative effect on cost efficiency, while ROA was significanly positive effect on cost efficiency. Based on the research results, it is hoped that banks can make adjustments to credit allowance reserves, streamline the number of human resources in collecting and recovery units related to credit management, and maximize the bank’s intermediation function.